Detection of foot contact and toe-off using kinematic data for treadmill running over a wide range of speeds - Okada, H.; Kurita, S.; Yabiku, S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purposes of this study were to propose a method for simply and accurately detecting the foot contact and toe-off events during treadmill running over a wide range of speeds and to examine the validity and accuracy of the method. Three patterns of foot-strike were distinguished from the foot kinematic data. The thresholds for foot contact and toe-off were determined inductively based on the minimum height of the heel or metatarsal for each foot-strike pattern with regard to running speed. The estimate for foot contact and toe off indicates that this method can apply over a wide range of speeds with high accuracy.